Trauma als Wissensarchiv Postkoloniale Erinnerungspraxis in der Sakralen Globalisierung am Beispiel der zeitgenössischen Umbanda im deutschsprachigen Europa - Scharf da Silva, Inga (Büchner-Verlag, 2022)
In the Brazilian religion Umbanda - which formed in the state of Rio de Janeiro at the beginning of the 20th century on the basis of African, indigenous and European religions - communication with spirit beings is central, recalling Brazilian history. Since the 1940s, it has spread worldwide and, from about 2010, also settled in German-speaking Europe in the course of transatlantic sacred globalization. Nevertheless, its spread has hardly been researched so far. Inga Scharf da Silva fills a research gap here by addressing the spiritual community of Ilê Axé Oxum Abalô (also called Terra Sagrada) on the basis of more than five years of ethnological field research. The community locates its mother house in the Swiss mountains in the canton of Appenzell and forms a transregional network with seven offshoots in Graz and Vienna, Zurich and Bern, Berlin and Cumuruxatiba in Brazil. Each chapter of the study is framed by the portrait of a deity (Orixá) as well as narratives from mythical lore and related to text passages from Oswald de Andrade's 'Manifesto Antropófago' and Umberto Eco's 'Foucault Pendulum'. In doing so, the author illustrates how the religious practice of trance as an incorporation of structures of consciousness can contribute to the reflection of the knowledge production of her religion and, beyond that, to a decolonization of thought in Europe.